What is the completely simplified form of the expression 2(1 – 3x) – (5x + 1)?
1 answer:
Answer:
i think it's 11x-1
Step-by-step explanation:
2(1-3x)-(5x+1)
2-6x-5x-1
2-11x-1
11x-1
You might be interested in
Answer:
2..25
Step-by-step explanation:
Answer:
5 but its probaly not right bc im just looking for pointsStep-by-step explanation:
D.........................................
Solution ,
length = 4m
breadth = 1.2m
height = 0.3m
Now
Area = l × b
= 4m × 1.2 m
= 4.8m²
Now
Volume = l × b × h
= 4m × 1.2m × 0.3m
= 1.44 m³
~Prasuna090154~